Enabling DPP derivatives to show multistate emission and developing the multifunctional materials by rational branching effect. (December 2018) - Zhang, Kai; Zhang, Zhenzhen; Fan, Xiaojing; Tang, Liangliang; Ding, Qi; Yang, Kun; Zhai, Min; Zhang, Haichang; Xue, Shanfeng; Yang, Wenjun
Abstract: Conventional polycyclic organic molecules exhibit aggregation-caused quenching (ACQ) effect, and some organic molecules with twisted and propeller backbones could be made into aggregation-induced/enhanced emission (AIE/AEE). However, it was interesting but challenging to enable conjugated molecules derived from fused (hetero)cycles with high photo- and thermal-stability to show multistate emission, rather than only dual emission in solution and crystalline states. In the current work, we presented a rational strategy for realizing multistate emission of 1, 4-diketo-pyrrolo [3, 4-c]pyrrole (DPP) derivatives by employing imidazole as the additional acceptor bridge and constructing the branched DPP-centered molecule with four peripheral donors (triphenylamine). The resulting D‒A‒D compound (TIDPP) emitted yellow in solution with the fluorescence efficiency of ca. 70%, and its crystalline and amorphous states as well as aqueous suspensions also exhibited impressive fluorescence efficiencies of 40–50%, filling the gap between ACQ and AIE of DPP derivatives. Moreover, aggregation could greatly red-shift emission spectra and significantly enhance the two-photon absorption cross section and excitation fluorescence in the aqueous suspension. TIDPP solid was also found to exhibit the unique mechanochromic blue-shift luminescence and the commendable OFET performance, signifying the existence of aggregation-induced molecular planarization. This work demonstrated that the rational branching effect could manipulate the aggregation emission behaviors and develop the multifunctional materials. Graphical abstract: The branched DPP-centered derivatives exhibiting bright multistate emission with strong aqueous 2PA and 2PEF, remarkable mechanohypsochromic luminescence, and commendable OFET performance. Image 1 Highlights: A synthetic strategy for new branched DPP-centered derivatives. A fully aromatic water-dispersible 2PA dye with strong deep-red 2PEF. The multiply branched D‒A′‒A‒A′‒D motif favoring OFET performance. A new mechanohypsochromic shift luminophor was obtained.